A portable system for two dimensional magnetic particle imaging. (February 2020) - Meribout, Mahmoud; Kalra, Mohit
Highlights: Experimental results indicate that an average magnetic field of 0.634 T can be achieved. Kaczmarz image reconstruction algorithm yields an error of less than 9%. The array features a magnetic field within the FFL region of around 0 T. Abstract: Magnetic Particle Imaging (MPI) is a novel approach which outperforms other powerful imaging techniques such as Magnetic Resonance Imaging (MRI) in terms of image resolution and image reconstruction execution time. However it uses high intensity electric current to generate relatively strong magnetic field which hinders its suitability to be used in hazardous areas and where portability is required. This paper suggests a new design of a portable and safe MPI system dedicated for process instrumentation and medical imaging applications. The apparatus consists of an array of Neodymium Iron Boron (NdFeB) magnets, evenly distributed according to Halbach arrangement, to generate a relatively strong homogeneous magnetic flux intensity. The aim of the design is to enhance the value of the magnetic flux density within the field of view (FOV) above the saturation value of the magnetic field corresponding to the paramagnetic particles. In addition, an increase of the FOV volume and a minimization of the number of pixels within the Free Field Line (FFL) with the lowest possible total weight are sought to improve the performance of the image reconstruction algorithm. This multivariable optimization problem which considers simultaneously the size of permanent magnets and the gap between adjacent magnets as design parameters was solved using two dimensional finite element method (2D-FEM) package. Both trapezoid and cuboid magnets elements design alternatives were considered during the optimization process using the Particle Swarm Optimization (PSO) algorithm. FEM simulation results indicate that an average magnetic flux density (Bavg  = 0.658 T) could be achieved using 12 permanent cuboid magnets elements of 20 mm length on each side. A hardware prototype using the optimized variables was constructed and the associated results match to a good extend the FEM simulation results, where an average magnetic flux density within the FOV region was found to be equal to 0.634 T could be obtained. Further assessment of the design on both phantom and real images using Kaczmarz image reconstruction algorithm demonstrates the effectiveness of the design where an image reconstruction error of less than 9% could be achieved using cuboid magnets using a magnet array of total weight around 1.8 kg. This may suggest that the proposed design can be a tangible alternative for next generation portable MPI systems which can be used either for biomedical applications or in hazardous areas associated to hydrocarbon pipelines within which traditional high current coils used to generate the static magnetic flux density are not allowed to be deployed.